The Cost of ICU Delirium and Coma in the Intensive Care Unit Patient. Issue 10 (October 2018) - Vasilevskis, Eduard E.; Chandrasekhar, Rameela; Holtze, Colin H.; Graves, John; Speroff, Theodore; Girard, Timothy D.; Patel, Mayur B.; Hughes, Christopher G.; Cao, Aize; Pandharipande, Pratik P.; Ely, E. Wesley
Abstract : Rationale: Intensive care unit (ICU) delirium is highly prevalent and a potentially avoidable hospital complication. The current cost of ICU delirium is unknown. Objectives: To specify the association between the daily occurrence of delirium in the ICU with costs of ICU care accounting for time-varying illness severity and death. Research Design: We performed a prospective cohort study within medical and surgical ICUs in a large academic medical center. Subjects: We analyzed critically ill patients (N=479) with respiratory failure and/or shock. Measures: Covariates included baseline factors (age, insurance, cognitive impairment, comorbidities, Acute Physiology and Chronic Health Evaluation II Score) and time-varying factors (sequential organ failure assessment score, mechanical ventilation, and severe sepsis). The primary analysis used a novel 3-stage regression method: first, estimation of the cumulative cost of delirium over 30 ICU days and then costs separated into those attributable to increased resource utilization among survivors and those that were avoided on the account of delirium's association with early mortality in the ICU. Results: The patient-level 30-day cumulative cost of ICU delirium attributable to increased resource utilization was $17, 838 (95% confidence interval, $11, 132–$23, 497). A combination of professional, dialysis, and bed costs accounted for the largest percentage of the incremental costs associated with ICU delirium. The 30-day cumulative incremental costs of ICU delirium that were avoided due to delirium-associated early mortality was $4654 (95% confidence interval, $2056–7869). Conclusions: Delirium is associated with substantial costs after accounting for time-varying illness severity and could be 20% higher (∼$22, 500) if not for its association with early ICU mortality. Abstract : Supplemental Digital Content is available in the text.